2021
DOI: 10.3390/life11070674
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ability of LARS2 Carboxy-Terminal Domain in Rescuing the MELAS Phenotype

Abstract: The m.3243A>G mutation within the mitochondrial mt-tRNALeu(UUR) gene is the most prevalent variant linked to mitochondrial encephalopathy with lactic acidosis and stroke-like episodes (MELAS) syndrome. This pathogenic mutation causes severe impairment of mitochondrial protein synthesis due to alterations of the mutated tRNA, such as reduced aminoacylation and a lack of post-transcriptional modification. In transmitochondrial cybrids, overexpression of human mitochondrial leucyl-tRNA synthetase (LARS2) has p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The construct to facilitate inducible expression of the isolated carboxy-terminal domain of LARS2 (Cterm), fused with Cox8 mitochondrial presequence at the N-terminus and FLAG-tag at the C-terminus, was prepared from the plasmid pcDNA6.2/Cox8-Cterm-FLAG [ 17 ]. The plasmid was NotI-/ApaI-digested, and the obtained insert was gel-eluted and ligated into the tetracycline-inducible pcDNA5/FRT/TO ® vector (Invitrogen, Waltham, MA, USA), according to standard cloning techniques.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The construct to facilitate inducible expression of the isolated carboxy-terminal domain of LARS2 (Cterm), fused with Cox8 mitochondrial presequence at the N-terminus and FLAG-tag at the C-terminus, was prepared from the plasmid pcDNA6.2/Cox8-Cterm-FLAG [ 17 ]. The plasmid was NotI-/ApaI-digested, and the obtained insert was gel-eluted and ligated into the tetracycline-inducible pcDNA5/FRT/TO ® vector (Invitrogen, Waltham, MA, USA), according to standard cloning techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research from our laboratory showed that RNA19 can in cellulo bind the carboxy-terminal domain of the human mitochondrial leucyl-tRNA synthetase, LARS2 [ 17 ]. Overexpression of this isolated domain, concisely named Cterm, has proven effective in rescuing the defective phenotype associated with the 3243A>G transition in human cells [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β Diabetes caused by oxidative phosphorylation is a rare type of diabetes. Mitochondrial tRNALeu (UUR) 3243A > G-spot mutation is the most common cause of mitochondrial diabetes (Capriglia et al, 2021). Kearns-Sayre syndrome, which is caused by a large deletion in the mitochondrial DNA, can also be associated with diabetes (Kamal et al, 2015) (Table 1).…”
Section: Mitochondrial Gene Mutations and Genetic Metabolic Abnormali...mentioning
confidence: 99%
“…Several papers have reported that overexpression of human mitochondrial leucyl-tRNA synthetase (LARS2) or its C-terminal domain (Cterm) has proven effective in rescuing the pathological phenotype in cellular models. In their research article, Capriglia et al [ 10 ] investigated the molecular basis underlying the ability of the Cterm domain in rescuing the MELAS phenotype. The cellular model employed, consisting of a trans-mitochondrial cybrid line with a >95% mutation load, confirmed the therapeutic potential of the Cterm peptide but also showed that its rescuing ability was independent of the mitochondrial bioenergetics, unlike what has previously been observed in other cybrid lines.…”
mentioning
confidence: 99%